THE PRIVATE LIBRARY OF HALINA DIDŽIULYTĖ-MOŠINSKIENĖ AND ALGIRDAS MOŠINSKIS - BEREZAUSKIENĖ, AUDRONĖ (Knygotyra, 2015)
The article presents an analysis of the family library which once belonged to the Lithuanian public and cultural figures living in exile, writer and pedagogue Halina Didžiulytė-Mošinskienė and her husband, engineer, architect and bibliophile Algirdas Mošinskis. The book collection stored in The Public Liudvika and Stanislovas Didžiuliai Library of Anykščiai District Municipality (hereinafter referred to as the Public Library) constitutes the fundamental source of the research. A short overview of the books of the private A. Mošinskis’ library, stored in the funds of the Library of Vilnius University and Martynas Mažvydas National Library of Lithuania is also presented. Employing the methods of traditional library science, the composition of the private library and its fate have been revealed, as well as its unique character has been disclosed. The analysis of the library has been conducted by way of using the aspects of theme and cultural history. It has been concluded that a private library served each Lithuanian living in exile as a certain kind of a tie binding him or her with their mother tongue and the environment of their culture. In the course of the research, it has been indicated that H. and A. Mošinskiai collected their private library inspired by their interests as public figures, Lithuanian patriots and representatives of culture, education and art. The research made into the private library of the well-educated cultural figures H. And A. Mošinskiai has proved that it was in the interests of educated Lithuanians living in exile to preserve the bond with their homeland and mother tongue. Moreover, it helped to evaluate the special nature of publishing process of Lithuanian books. The importance of preserving the Lithuanian books published in exile that are available in the private library of H. and A. Mošinskiai was related to the fact alone that they were released in very small numbers of copies. The average number of copies Lithuanian books used to be published in was a mere 1.000 copies. The library under the research distinguishes itself by its definite universality, determined by the cultural and professional interests of the owners H. and A. Mošinskiai. A considerable part of the book collection is made up of books presented to the owners by their authors, friends and other close people. The value of the books is enhanced by the autographs and inscriptions found in them that helped identify the owners’ ties with the Lithuanian writers and other cultural figures in exile. They also brought some light to the owners’ biographical facts. The contents of the found inscriptions have confirmed the fact that a private library played part of a connection with their mother tongue and the environment of Lithuanian culture to the people deprived of their homeland. In conclusion, it can be stated that the private libraries once owned by Lithuanians living in exile were doomed to disappear, bearing in mind the fact that there were no institutions responsible for taking over the book funds under their custody in the event of the owner’s death. The preservation and continuation of the book collections only became possible when they were trasferred to the institutions based in Lithuania, and best of all, if they were bequeathed following the owner’s Last Will, the execution of which was obligatory to the heirs. No data were found on the library’s catalogue, leaving it beyond the field of the research. The book collection in the private library of A. Mošinskis, stored in the Library of Vilnius University, has not been given a more profound analysis either. An in-depth reconstruction of the private library of H. and A. Mošinskiai still remains a future task.
Keywords: ...